New Records of the Egg Development Phase of Varuna litterata in the Lower Serayu River, Central Java - sinaga, sorbakti; Widodo , Maheno Sri; Maimunah, Yunita (Journal of Aquaculture and Fish Health, 2024)
One of the Brachyura crabs found in the lower reaches of the Serayu River is Varuna litterata, also known as the "herring bow crab". This crab usually inhabits shallow tidal areas and hides under rocks, logs, or dead leaves. It is a highly adapted crab found in a wide range of salinities. V. litterata is also a fishery product consumed in Thailand, the Philippines, and Indonesia. This research was conducted in the Lower Serayu River, Central Java, which consists of three observation stations, namely: 1) the first station is located above the dam with fresh water, 2) the second station is below the dam with fresh water properties and 3) the third station is downstream (estuary) of the Serayu River with brackish water. This research was conducted for four months, from October 2023 to January 2024. This study aimed to determine the level of egg development in V. litterata. The results showed that V. litterata experienced four stages in egg development and then hatched into zoea. At the initial development stage, V. litterata eggs will be purple; in the second stage, the eggs will turn reddish; in the third development stage, the eggs will turn orange to brownish; and in the fourth stage, the eggs will develop and become black. V. litterata that will spawn will migrate to brackish waters to hatch their eggs. V. litterata produces 20,708 - 85,886 eggs with an average egg diameter of 0.440 - 0.466 mm.